Asymptomatic Gastric Metastasis From Ovarian Adenocarcinoma Presented as Gastric Subepithelial Tumor: Case Report - Qiyu Yang; Aihua Li; Zeyu Lu; Shihang Tang (JGH Open, 2025)
ABSTRACT Background Ovarian tumor metastasis to the stomach is uncommon. Clinical manifestations of metastasis to the stomach are variable and lack features. Gastric metastasis resembling a subepithelial tumor is unusual, making the diagnosis challenging. Case Presentation Here, we reported a case of gastric metastasis from ovarian adenocarcinoma presenting as a subepithelial tumor diagnosed by endoscopic ultrasound‐guided tissue acquisition. Conclusion This case provides significant reference value and serves as a cautionary reminder for the diagnosis and management of gastric subepithelial tumors.